Neutrophil extracellular traps generation and degradation in patients with granulomatosis with polyangiitis and systemic lupus erythematosus - Michal Przemyslaw Pruchniak; Magdalena Ostafin; Malgorzata Wachowska; Michal Jakubaszek; Brygida Kwiatkowska; Marzena Olesinska; Katarzyna Zycinska; Urszula Demkow (Taylor & Francis Group, 2019)
Neutrophils are one of the first cells to arrive at the site of infection, where they apply several strategies to kill pathogens: degranulation, respiratory burst, phagocytosis, and release of neutrophil extracellular traps (NETs). Recent discoveries try to connect NETs formation with autoimmune diseases, like systemic lupus erythematosus (SLE) or granulomatosis with polyangiitis (GPA) and place them among one of the factors responsible for disease pathogenesis. The aim of the study was to assess the NETotic capabilities of neutrophils obtained from freshly diagnosed autoimmune patients versus healthy controls. Further investigation involved assessing NETs production among treated patients. In the latter step, NETs degradation potency of collected sera from non-treated patients was checked. Lastly, the polymorphisms of the DNASE I gene among tested subjects were checked. NETs formation was measured in a neutrophil culture by fluorometry, while degradation assessment was performed with patients' sera and extracellular source of DNA. Additionally, Sanger sequencing was used to check potential SNP mutations between patients. About 121 subjects were enrolled into this study, 54 of them with a diagnosed autoimmune disorder. Neutrophils stimulated with NETosis inducers were able to release NETs in all cases. We have found that disease affected patients produce NETs more rapidly and in larger quantities than control groups, with up to 82.5% more released. Most importantly, we showed a difference between the diseases themselves. NETs release was 68.5% higher in GPA samples when compared to SLE ones while stimulated with Calcium Ionophore. Serum nucleases were less effective at degrading NETs in both autoimmune diseases, with a reduction in degradation of 20.9% observed for GPA and 18.2% for SLE when compared with the controls. Potential therapies targeting neutrophils and NETs should be specifically tailored to the type of the disease. Since there are significant differences between NETs release and disease type, a standard neutrophil targeted therapy could prevent over-generation of traps in some cases, while in others it would deplete the cells, leaving the immune system unresponsive to primary infections.